Responsiveness to an erythropoiesis-stimulating agent is correlated with body composition in patients undergoing chronic hemodialysis - Lee, Hyang Yun; Suh, Suk-Won; Hwang, Jin Ho; Shin, Jungho (Frontiers in Nutrition, 2022)
Background Resistance to erythropoiesis-stimulating agents (ESA) is associated with adverse outcomes in patients undergoing chronic hemodialysis. However, the impact of body composition on ESA response remains uncertain. This study retrospectively investigated whether there is an association between the ESA resistance index (ERI) and body composition in patients undergoing chronic hemodialysis. Methods Multifrequency bioelectrical impedance analysis was used to measure body composition every six months. The ERI was calculated by dividing the weekly body weight-adjusted erythropoietin dose by the hemoglobin concentration. The ERI values were recorded every three months. Results A total of 123 patients were followed up for 24 (interquartile range 5, 75) months. The ERI was negatively correlated with body mass index, arm circumference, arm muscle circumference, body fat percentage, and visceral fat area (P = 0.057, 0.001, 0.017, 0.063, and 0.041, respectively). Patients with a higher mean ERI during the study period had an increased risk of all-cause mortality, cardiovascular events, and infection requiring hospitalization than those with a lower mean ERI (P = 0.027, 0.021, and 0.037, respectively). We also evaluated the association between the slope of body composition parameters and the ERI trend over time and found that the ERI increased over time in patients who had an increased ratio of extracellular water to total body water (P = 0.002) as well as decreased arm circumference, arm muscle circumference, visceral fat area, and phase angle (P = 0.001, P < 0.001, P = 0.036, and 0.002). Conclusion ESA responsiveness appears to be associated with body composition in patients undergoing chronic hemodialysis. Therefore, measures improving body composition, such as nutrition and exercise, may have a favorable effect on the response to ESA.